Organizational Dehumanization and its role in generating cynicism in the workplace: A field study in the Ministry of Labor and Social Affairs (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to study the correlation and influence of the independent variable organizational Dehumanization in generating the dependent variable cynicism in the workplace   This is to reduce cynicism in the workplace, as it is one of the negative phenomena spread in society in general and in the Ministry of Labor and Social Affairs in particular. The research also aims to shed light on one of the modern vocabulary that is dealt with extensively by management writers, which is organizational Dehumanization, and what are the consequences and negative effects that it can have in the Ministry of Labor and Social Affairs. From here, the main problem of the research was identified, which is (What are the reasons that lead to the appearance of cynicism in the Ministry of Labor and Social Affairs? Does the Ministry of Labor and Social Affairs suffer from organizational Dehumanization?). The questionnaire was the main tool for collecting data and information. The research was conducted at the center of the Iraqi Ministry of Labor and Social Affairs, and the research community was represented by all employees at various administrative levels, by choosing a random sample, as (123) questionnaires were distributed, and (104) audited and measurable questionnaires were received. Which represents (85%) of the total distributed questionnaires. In order to process the data, many statistical methods were used, most notably the arithmetic mean, standard deviation, Pearson correlation coefficient, and structural equations model. The most important findings of the research is that there is a significant impact of organizational humanity in generating cynicism in the workplace in the Ministry of Labor and Social Affairs.